2017
DOI: 10.1186/s10194-017-0721-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression of home cage wheel running: a reliable and clinically relevant method to assess migraine pain in rats

Abstract: BackgroundThe development of new anti-migraine treatments is limited by the difficulty inassessing migraine pain in laboratory animals. Depression of activity is one of the few diagnostic criteria formigraine that can be mimicked in rats. The goal of the present study was to test the hypothesis thatdepression of home cage wheel running is a reliable and clinically relevant method to assess migraine painin rats.MethodsAdult female rats were implanted with a cannula to inject allyl isothiocyanate (AITC) onto the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
3
29
0
1
Order By: Relevance
“…Since then, a range of other pain conditions have been shown to depress wheel running in rats and mice. These include hindpaw inflammation, arthritis, migraine-like pain, neuropathic pain, surgical pain, and more (Cattaruzza et al, 2013;Kandasamy et al, 2016Kandasamy et al, , 2017bKendall et al, 2016;Pitzer et al, 2016aPitzer et al, , 2016bStevenson et al, 2011;Tang et al, 2016;Whitehead et al, 2017).…”
Section: Wheel Runningmentioning
confidence: 99%
“…Since then, a range of other pain conditions have been shown to depress wheel running in rats and mice. These include hindpaw inflammation, arthritis, migraine-like pain, neuropathic pain, surgical pain, and more (Cattaruzza et al, 2013;Kandasamy et al, 2016Kandasamy et al, , 2017bKendall et al, 2016;Pitzer et al, 2016aPitzer et al, , 2016bStevenson et al, 2011;Tang et al, 2016;Whitehead et al, 2017).…”
Section: Wheel Runningmentioning
confidence: 99%
“…The thermo-TRP ankyrin type-1 (TRPA1) channels - sensors of oxidative, nitrative and electrophilic stress – have been involved in different models of pain diseases [ 2 ] and seem to play a key role also in the mechanisms of migraine pain. Indeed, their activation is operated by a plethora of exogenous and endogenous stimuli, among which there are many migraine triggers [ 1 , 3 , 4 ]. TRPA1 channels can be found in many types of cells and tissue, but they are mostly expressed in sensory neurons [ 5 , 6 ]; they are implicated in meningeal nociceptive and vascular responses involving neurogenic dural vasodilatation and plasma extravasation.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that home cage wheel running provides an objective and clinically relevant measure of the duration and magnitude of pain in rats (Kandasamy et al, 2016; 2017a; 2017b). If depression of home cage wheel running is a measure of an abnormal physiological state as these previous studies indicate, then spontaneous opioid withdrawal should also cause depression of home cage wheel running.…”
mentioning
confidence: 99%